2020
DOI: 10.3389/fpsyt.2020.608476
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness, Social Isolation and Their Difference: A Cross-Diagnostic Study in Persistent Depressive Disorder and Borderline Personality Disorder

Abstract: Background: Interpersonal difficulties are a key feature of persistent depressive disorder (PDD) and borderline personality disorder (BPD). Caught in a vicious circle of dysfunctional interpersonal transaction, PDD and BPD patients are at great risk of experiencing prolonged loneliness. Loneliness, in turn, has been associated with the development of mental disorders and chronic illness trajectories. Besides, several factors may contribute to the experience of loneliness across the lifespan, such as social net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 104 publications
(140 reference statements)
6
41
0
Order By: Relevance
“…However, it should be noted that we assessed severe and traumatic adversities in childhood, which may not have the same beneficial effects on prosocial attitudes and motivation in terms of posttraumatic growth. Further, our findings are consistent with a recent study that found an association between emotional abuse with loneliness, with the association mediated by increased rejection sensitivity ( 45 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, it should be noted that we assessed severe and traumatic adversities in childhood, which may not have the same beneficial effects on prosocial attitudes and motivation in terms of posttraumatic growth. Further, our findings are consistent with a recent study that found an association between emotional abuse with loneliness, with the association mediated by increased rejection sensitivity ( 45 ).…”
Section: Discussionsupporting
confidence: 93%
“…Patients with PDD reported higher levels of childhood adversity (CTQ total score: M = 53.17, SD = 16.36) compared to a representative sample ( 43 ) as well as a healthy control group from a recent other study ( 45 ), especially regarding emotional abuse [ M = 13.72, SD = 5.77 vs. M = 6.49, SD = 2.60 ( 43 ) and M = 7.0, SD = 3.5 ( 45 ), respectively] and emotional neglect M = 16.40, SD = 5.34 vs. M = 10.05, SD = 4.23 ( 43 ) and M = 8.3, SD = 3.1 ( 45 ), respectively; see Supplementary Table 2 for details]. Overall childhood adversity was significantly negatively correlated with connectedness to family members ( Table 2 ).…”
Section: Resultsmentioning
confidence: 92%
“…Foxhall et al (29) have proposed rejection sensitivity to be linked to both CM (i.e., particularly emotional abuse and neglect) and to BPD. Similarly, rejection sensitivity appears to be elevated in PDD compared to healthy controls (27,28) and was correlated not only with BPD symptoms but also with self-reported depression. Rejection sensitivity may in fact be a mediating factor between childhood adversity and later psychopathology though this hypothesis still needs to be tested in larger cross-diagnostic studies (29).…”
Section: Discussionmentioning
confidence: 89%
“…One putative link from CM to later psychopathology may be an induced trait of rejection sensitivity, i.e., oversensitivity to and expectation of social rejection ( 26 ). Rejection sensitivity has been found to be associated with PDD ( 27 , 28 ) and BPD ( 29 ). Thus, rejection sensitivity may theoretically mediate the path from CM to both PDD and BPD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our results indicated that the visually impaired had significantly lower scores on all subscales but the Growth and development one. We would intuitively expect that those who may feel so poignantly different from the rest of the population, who live using other senses instead of sight which is a major sense used by non-visually impaired individuals (see Osaba et al, 2019), may be experiencing social inadequacy in a world which is not, fundamentally, geared to accommodate them, and thus may feel alienated, to a larger extent than the regular population (see Nenov-Matt et al, 2020 for a discussion of the loneliness-social isolation interaction). However, the present findings showed a significantly different picture, where the general population had significantly higher subscale scores than the visually impaired.…”
Section: Discussionmentioning
confidence: 99%